Diffuse Large B-Cell Lymphoma Promotes Endothelial-to-Mesenchymal Transition via WNT10A/Beta-Catenin/Snail Signaling - Sun, Xianting; Fang, Jianchen; Ye, Fen; Zhang, Shuxian; Huang, Honghui; Hou, Jian; Wang, Ting (Frontiers in Oncology, 2022)
Diffuse large B-cell lymphoma (DLBCL) is one type of highly heterogeneous lymphoid malignancy with 30% 40% of patients experiencing treatment failure. Novel risk stratification and therapeutic approaches for DLBCL are urgently needed. Endothelial-to-mesenchymal transition (EndMT), which contributes to tumor angiogenesis, metastasis, drug resistance, and cancer-associated fibroblast generation, has been detected in the microenvironment of many types of cancers. However, the existence of EndMT in the hematological malignancies microenvironment remains unknown. Here, we identified the existence of EndMT in DLBCL-associated endothelial cells and the clinical relevance of EndMT markers in DLBCL, which was associated with advanced clinical stage and poor prognosis. In vitro experiments confirmed that DLBCL cells stimulated angiogenesis and EndMT of human umbilical vein endothelial cells (HUVECs). We further unveiled the molecular mechanisms underlying this process. We demonstrated that WNT10A, a WNT family member overexpressed in DLBCL tissues and correlated with clinical features in DLBCL, promoted EndMT through glycogen synthase kinase 3β (GSK3β)/β-catenin/snail signaling. WNT10A inhibited the binding of GSK3β to β-catenin/snail, resulting in β-catenin and snail nuclear accumulation and target gene transcription. Silencing β-catenin and snail respectively attenuated WNT10A-induced angiogenesis and EndMT. The interplay between β-catenin-dependent and snail-dependent signaling was also confirmed in this study. Collectively, these findings identified that WNT10A/GSK3β/β-catenin/snail pathway performed vital roles in DLBCL-induced EndMT and indicated that EndMT markers and WNT10A may serve as novel predictors of clinical outcome.